2014
DOI: 10.1002/vnl.21423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler loading and coconut oil coupling agent on properties of low‐density polyethylene and palm kernel shell eco‐composites

Abstract: Palm kernel shell (PKS), a waste from the oil palm industry, has been utilized as filler in low-density polyethylene (LDPE) eco-composites in the present work. The effect of PKS content and coconut oil coupling agent (COCA) on tensile properties, water absorption, and morphological and thermal properties of LDPE/PKS eco-composites was investigated. The results show the increase of PKS content decreased the tensile strength and elongation at break, but increased the tensile modulus, crystallinity, and water abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The char formation also contributed to high percentage of residue content of rPS/DHF composites. The similar findings regarding to effect of char formation influenced the thermal properties of composites also reported by others researcher [21][22]. In conclusion, addition of more fiber content increased the tensile strength and modulus of rPS/DHF composites increased, but decreased the elongation at break.…”
Section: Tensile Propertiessupporting
confidence: 89%
“…The char formation also contributed to high percentage of residue content of rPS/DHF composites. The similar findings regarding to effect of char formation influenced the thermal properties of composites also reported by others researcher [21][22]. In conclusion, addition of more fiber content increased the tensile strength and modulus of rPS/DHF composites increased, but decreased the elongation at break.…”
Section: Tensile Propertiessupporting
confidence: 89%
“…The OPS nanofillers were basically hydrophilic. According to Husseinsyah et al (2014), OPS consists of many hydroxyl groups that contribute to its hydrophilic nature because it has a high tendency to absorb water. Therefore, the addition of OPS nanofillers increased the number of hydroxyl groups in the matrix and caused the nanocomposite films to become more accessible to water.…”
Section: Hydrophilicity Of Bio-nanocomposite Filmsmentioning
confidence: 99%
“…Figure 2, the water absorption of UPE/OPS composites increased with OPS content, which indicated that water absorption of composite is higher than the UPE matrix. As proposed by Salmah et al [13], the structure of OPS consists of hydroxyl groups that give the hydrophilic properties of absorbing water which has been proved by pure polyester that shows the lowest percentage in water absorption. Moreover, the presence of microcracks and gaps between OPS and UPE enhance the diffusion of water and thus the water absorption increases with the increase of OPS content.…”
Section: Resultsmentioning
confidence: 95%
“…Since the addition of OPS particles to UPE matrix developed a rigid interface, it will inhibit the matrix chain mobility and cause the tensile modulus of UPE/OPS to increase with the addition of OPS to 10 vol%. This is attributed to stiffer and more rigid composites [13]. For 20 vol% of OPS, the value showed lower tensile modulus (stiffness) of the composites which in turn increased the elongation at break as a stiff material reducing deformability of a rigid interface between the OPS and matrix and changed its shape slightly under elastic loads [14].…”
Section: Resultsmentioning
confidence: 99%